2007
DOI: 10.1086/521382
|View full text |Cite
|
Sign up to set email alerts
|

Variable Very High Energy γ‐Ray Emission from Markarian 501

Abstract: The blazar Mrk 501 was observed at energies above 0.10 TeV with the MAGIC Telescope from 2005 May through July. The high sensitivity of the instrument enabled the determination of the flux and spectrum of the source on a night-by-night basis. Throughout our observational campaign, the flux from Mrk 501 was found to vary by an order of magnitude. Intranight flux variability with flux-doubling times down to 2 minutes was observed during the two most active nights, namely, June 30 and July 9. These are the fastes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
462
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(488 citation statements)
references
References 67 publications
23
462
1
2
Order By: Relevance
“…Observations of fast variability for a number of blazars have already been reported in the literature (Aharonian et al 2007;Albert et al 2007;Abramowski et al 2010Abramowski et al , 2012Acciari et al 2010Acciari et al , 2008Arlen et al 2013). As there is no unique way of measuring the variability, the time scales reported in the literature are often derived in different manners and have to be put into the same scale.…”
Section: Data Selection and Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Observations of fast variability for a number of blazars have already been reported in the literature (Aharonian et al 2007;Albert et al 2007;Abramowski et al 2010Abramowski et al , 2012Acciari et al 2010Acciari et al , 2008Arlen et al 2013). As there is no unique way of measuring the variability, the time scales reported in the literature are often derived in different manners and have to be put into the same scale.…”
Section: Data Selection and Analysismentioning
confidence: 84%
“…However, the observed fast variability of the blazar γ-ray emission -down to (sub-)hour time scales (Aharonian et al 2007;Albert et al 2007;Neronov et al 2008;Abramowski et al 2010;Foschini et al 2011;Neronov & Vovk 2011;Sbarrato et al 2011;Vovk & Neronov 2013) -suggests that the gammaray emission region is very compact, much smaller than the transverse size of the jet at parsec distances from the SMBH.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang & Zhang 2014). This scenario can also explain the ultra-fast variability (e.g., several minutes) as found in some blazars at TeV energies (e.g., Aharonian et al 2007;Albert et al 2007;Aleksic et al 2014). Sonbas et al (2014) found that the MTS becomes shorter as the gamma-ray luminosity (or Lorentz factor) increases in GRBs.…”
Section: Introductionmentioning
confidence: 83%
“…The typical minimum variability timescale (MTS) for blazars is around one day (e.g., Vovk & Neronov 2013), where ultra-fast variability as short as 3-5 min at TeV energies is also found in some blazars (e.g., Aharonian et al 2007;Albert et al 2007;Aleksic et al 2014). The typical MTS of GRBs is around 0.5 s with the shortest timescale on the order of 10 ms (e.g., MacLachlan et al 2013;, where the MTS is much shorter than the overall duration (e.g., T90).…”
Section: Introductionmentioning
confidence: 99%
“…Vary rapid variations of the γ-ray flux, with inferred doubling time-scales down to few minutes, have been observed in several blazars (both BL Lacs and FSRQ), most notably PKS 2155-304 [43], Mkn 501 [44], BL Lac [45], PKS 1222+21 [46], IC 310 ( [47] although the precise classification of this source is still matter of debate) and, last but not least, 3C279 (at GeV energies by pointed observations with Fermi/LAT, [48]). Such small timescales directly imply, via the standard causality argument, very compact emission regions, with radii not exceeding r < ct var δ ≈ FIGURE 1.…”
Section: Some Open Issuesmentioning
confidence: 99%